Review of Childhood Obesity (Balar Athidhoola Rogam) in Traditional Siddha Indian Medicine - Soundararajan, D.K. (Current Traditional Medicine, 2015)
Childhood Obesity (Athi Dhoola noi) starts over from the young age due to various causative factors even it may deal from the infancy. The obesity in such age causes various complications to the each and every body tissues right from the connective tissues to the genital tissues. The susceptibility with the obesity for cardiac and diabetic issues is high since it interferes with its metabolism. Over the past three decade the prevalence of overweight and obesity has increased substantially [1]. Globally, an estimated 170 million children (aged < 18 years) are estimated to be overweight, and in some countries, the number of overweight children has trebled since 1980. The high prevalence of overweight and obesity has serious health consequences. Raised body mass index (BMI) is a major risk factor for diseases such as cardiovascular disease, type 2 diabetes and many cancers (including, colorectal cancer, kidney cancer and Oesophageal cancer). These diseases often referred to as Non-Communicable Diseases (NCDs), not only cause premature mortality but also long-term morbidity. In addition, overweight and obesity in children are associated with significant reductions in quality of life (QoL) and a greater risk of teasing, bullying and social isolation and Stigmatization. Due to the rapid increase in obesity prevalence and the serious health consequences, obesity is commonly considered as one of the most serious health challenges of the early 21st century. This article briefly explains the importance and it negative impacts of Childhood obesity in a proposed manner.
Keywords: Siddha Medicine